Use case report on scenarios of water availability and use in the Central Highland Ecoregions Foodscapes (CHEF) of Kenya - Owusu, Afua; Matheswaran, Karthikeyan; Velpuri, Naga Manohar; Magesa, R.; Schmitter, Petra S. (International Water Management Institute, 2024)
This report examines water availability and usage in Kenya’s Central Highland Ecoregions Foodscapes (CHEF), highlighting the role of data-driven tools in sustainable agricultural water management. The International Water Management Institute (IWMI) has developed the Scale Invariant Water Accounting Plus (SIWA+) framework and the Securing Water Use in Agriculture (SWAG) tool to address key water challenges. SIWA+ provides insights into water inflows, outflows, and consumption, aiding policymakers in mitigating water scarcity. SWAG assesses crop water requirements, helping identify water deficits and surpluses to optimize irrigation strategies.